Extraordinarily ordinary : Us weekly and the rise of reality television celebrity - Meyers, Erin A. (Rutgers University Press, 2020)
"Extraordinarily Ordinary offers a critical analysis of the production of a distinct form of twenty-first century celebrity constructed through the exploding coverage of reality television cast members in Us Weekly magazine, unpacking the ways in which the magazine helped promote a broader intensification of discourses of ordinariness or "just being yourself" in the production of contemporary celebrity"--